RETRACTED: Nexus Between Economic Development and Energy Poverty to Gain Energy Efficiency: Empirical Evidence From China - Anser, Muhammad Khalid; Yusop, Zulkornain; Abbas, Shujaat; Ali, Sajid; Ahmad, Munir (Frontiers in Energy Research, 2022)
Mediating the nexus between economic development, energy poverty, and energy efficiency has become a major issue for governments. Evidence from China shows that both sectors have an important role in determining economic development policies and alleviating poverty. Economic development in China is examined experimentally in this research. This study makes use of the Data Envelopment Analysis and the entropy approach between 2007/08 and 2010/11 on the 17 provinces of china. For every unit increase in economic growth pressure, the development indicator of energy efficiency falls by 3.4 percent. Energy poverty and energy efficiency in China are strongly linked to economic development, according to the model's economic development findings.. Economic inequalities in China have increased as a result of greater economic development. or China's economic development to be of high quality, we believe that our results will be useful in understanding the function of national economic growth management and coordination in wealth distribution and energy use. For rural and male-headed families, the economic development is more consistent. Employees are most likely to be economic development from an increase in economic development, which is expected to reduce energy poverty the most and improve energy efficiency the most.